Integrated environmental analysis of the main cork products in southern Europe (Catalonia – Spain) (Journal of Cleaner Production)
This study presents an environmental analysis of the cork sector by integrating and evaluating the production of the products that are most commonly made of cork: natural cork stoppers, champagne cork stoppers, white cork granulate and black cork granulate, in order to propose environmental strategies that could contribute to minimising the potential impacts of the cork sector. Life Cycle Assessment (LCA) was the methodology used in order to assess the potential environmental impacts of the cork sector and its main products. Inventory was supported by 15 companies in Catalonia. Different environmental midpoint impact categories were reported and analysed according to CML 2001 method such as Abiotic Depletion (ADP), Acidification Potential (AP), Eutrophication Potential (EP), and many other. Also, the Global Warming Potential (GWP 100 years), was assessed, and it was found that the cork sector contributed to fixing carbon dioxide and consequently can help to mitigate climate change, besides generating cork products. Specifically, 3.4 tonnes of CO2 eq. were emitted to convert a tonne of raw cork from the forest into products, while 18 tonnes of CO2 are fixed per tonne as a result of the existence of cork oak forests; the resulting balance was that 14.6 tonnes of CO2 are fixed. A sensitivity analysis was carried out of the distribution of environmental impacts between products; it was observed that allocation rules were an important point of the assessment. The use of cork, a natural, renewable and local material, can help to reduce the environmental impact of products. The use of cork stoppers contributes to reducing the carbon footprint of beverages such as wines, champagnes, beers, ciders, brandies and many other beverages.